Living Qur'an in Islamic Educational Institutions at The Elementary Level: A Case Study of Miftahul Falaah Islamic Elementary School of Kediri City - Umam, Khaerul; Rahmaniya, Diana; Zulaihah, Evy; Husna, Fina Fatihatul; Maria, Haniam; Wahyudin, Muhamad Nur; Romadoniah (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The purpose of this study is to explore and describe how the implementation of the Living Qur'an concept is carried out in Islamic education at the primary level, as well as how it impacts on students' character and attitude. Data were collected through observation, interviews, and documentation and then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that MI Miftahul Falaah Kediri City has implemented the concept of Living Qur'an in the learning process. Implementation is accomplished by teaching the Qur'an, learning Islamic values through real examples, and habituation in the correct worship procedures. As a result, students were able to understand the Qur'an holistically and practice it in everyday life. In addition, the implementation of Living Qur'an also has a positive impact on student characteristics and attitudes, such as increasing social care, tolerance, and respect for differences. This is because students have become accustomed to applying Islamic values to their daily lives. In addition, this study found that MI Miftahul Falaah's efforts in reviving the Quran were carried out in various ways, including: 1) Implementing Tahfidz Learning; 2) Getting used to Reciting short letters before learning begins; 3) Implementing Qur'an recitation learning; and 4) Yasin recitation. Contribution: This research strengthens the Living Qur'an model in primary education, effectively shaping students' character based on Islamic values.